21.0k views
5 votes
1. select all equations 2. select all equations 3.select all equations

1. select all equations 2. select all equations 3.select all equations-example-1
User Parthiv
by
5.3k points

1 Answer

6 votes

The correct option C and F

Step-by-step explanation:

x² + 6x = 16

we need to check the other options to find out its equivalence.

a) x² + 6x + 9 = 0

Rewritting the equation above: x² + 6x - 16 = 0

From the above, we can see they are different

b) x² + 6x + 9 = 16

rewritting: x² + 6x + 9 - 16 = 0

x² + 6x - 7 = 0

This is not equivalent to x² + 6x - 16 = 0

c) x² + 6x + 9 = 25

x² + 6x + 9 -25 = 0

x² + 6x -16 = 0

x² + 6x = 16

This is equivalent to x² + 6x = 16

d) (x + 3)² = 0

(x+3)(x+3) = 0

x(x+3)+3(x+3) = 0

x² +3x +3x + 9 = 0

x² + 6x + 9 = 0

This is not equivalent to x² + 6x - 16 = 0

e) (x+3)² = 16

(x+3)(x+3) = 16

x(x+3)+3(x+3) = 16

x² +3x +3x + 9 = 16

x² + 6x + 9 = 16

x² + 6x = 16 - 9

x² + 6x = 7

This is not equivalent to x² + 6x - 16 = 0

f) (x+3)² = 25

(x+3)(x+3) = 25

x(x+3)+3(x+3) = 25

x² +3x +3x + 9 = 25

x² + 6x + 9 = 25

x² + 6x = 25 - 9

x² + 6x = 16

This is equivalent to x² + 6x = 16

The correct option C and FF

x(x+3)+3(x+3) = 16

x² +3x +3x + 9 = 16

x² + 6x + 9 = 0

User Mazlix
by
5.0k points